(untitled) (Journal of Educational Sciences, 2023)
This article examines the impact of per-capita school funding in Kazakhstan on the improvement of instruction of students with SEN. It offers an extensive literature review on inclusive education funding models internationally and interprets Kazakhstan’s experience in this context. Data in this article comes from a survey of almost 500 urban general day school directors in Kazakhstan’s regions. The article answers three research questions. First, how do urban day schools differ in terms of presence of students with SEN? Second, how do urban day schools that teach students with SEN differ in their policies and practices towards this group of students, and whether they differ by the type of funding that they receive? Third, how do schools that receive PCF assess the impact of this funding on the improvement of instruction of students with SEN? This research finds that factors that determine whether students with SEN are enrolled at the school are the selectiveness of admission to school, the language of instruction, the presence of school-level policy towards students with SEN, and additional staff hired for students with SEN. It shows that schools, which receive PCF, controlled for the size of the urban location, are two times more likely to have students with SEN in general education classrooms compared to schools that do not receive PCF. Schools that have home-schooled students with SEN are less likely to include these students in general education classes. Further research should examine what is the role of schools in maintaining students with SEN in homeschooling. Findings in this research indicate that teacher professional capacity, the quality of school infrastructure, and the decision-making freedom of school principals form important bases for the effectiveness of per-capita school funding to enable the development of inclusive education in Kazakhstan. Key words: Per-capita funding, throughput funding, outcomes-based funding, school finance, students with special needs, inclusive education, policy analysis.